Deguelin inhibits the proliferation of human multiple myeloma cells by inducing apoptosis and G2/M cell cycle arrest: Involvement of Akt and p38 MAPK signalling pathway - Sun Kening; Chen Ping; Zhang Liang; Lu Zhidong; Jin Qunhua (Acta Pharmaceutica)
Deguelin exhibits antiproliferative activity against various cancer cell types. Previous studies have reported that deguelin exhibits pro-apoptotic activity against human cancer cells. The current study aimed at further elaborating the anticancer effects of deguelin against multiple myeloma cells. Cell growth estimations were made through MTT assay. Phase contrast microscopy was used for the analysis of the viability of multiple myeloma cells. Colony formation from multiple myeloma cells was studied using a clonogenic assay. Antioxidative assays for determining levels of glutathione (GSH) and superoxide dismutase (SOD) were carried out after treating multiple myeloma cells with deguelin. The apoptosis of multiple myeloma cells was studied using AO/EB and Annexin V-FITC/PI staining methods. Multiple myeloma cell cycle analysis was performed through flow cytometry. mRNA expression levels were depicted using qRT-PCR. Migration and invasion of multiple myeloma cells were determined with the wound-healing and transwell assays, respectively. Deguelin specifically inhibited the multiple myeloma cell growth while the normal plasma cells were minimally affected. Multiple myeloma cells when treated with deguelin exhibited remarkably lower viability and colony-forming ability. Multiple myeloma cells treated with deguelin produced more SOD and had higher GSH levels. The multiple myeloma cell growth, migration, and invasion were significantly declined by in vitro administration of deguelin. In conclusion, deguelin treatment, when applied in vitro, induced apoptotic cell death and resulted in mitotic cessation at the G2/M phase through modulation of cell cycle regulatory mRNAs in multiple myeloma cells.